2006
DOI: 10.1016/j.jclinepi.2005.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A review of the application of propensity score methods yielded increasing use, advantages in specific settings, but not substantially different estimates compared with conventional multivariable methods

Abstract: Publication of results based on propensity score methods has increased dramatically, but there is little evidence that these methods yield substantially different estimates compared with conventional multivariable methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
507
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 585 publications
(529 citation statements)
references
References 226 publications
(137 reference statements)
16
507
0
6
Order By: Relevance
“…The conclusions from these studies were inconsistent. Two studies 66,68 concluded that estimates obtained from regression analysis are similar to those obtained using propensity scoring. However, two studies 64,67 also came to the opposite conclusion, that estimates obtained from regression analysis and propensity scoring differ significantly.…”
Section: Effectiveness Of Adjustment Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The conclusions from these studies were inconsistent. Two studies 66,68 concluded that estimates obtained from regression analysis are similar to those obtained using propensity scoring. However, two studies 64,67 also came to the opposite conclusion, that estimates obtained from regression analysis and propensity scoring differ significantly.…”
Section: Effectiveness Of Adjustment Methodsmentioning
confidence: 91%
“…A summary of the studies that have looked at methods of adjustment for confounding bias in NRSs and how reliable they are [62][63][64][65][66][67][68][69][70] is presented in Appendix 3. Overall, it is unclear which methods are most appropriate in certain circumstances and further research is needed.…”
Section: Adjustment For Bias In Non-randomised Studiesmentioning
confidence: 99%
“…Indeed, systematic differences between statin users and non-users have been found to influence estimates of the effect of exposure to the drugs [17,18]. A propensity score is a measure of how likely an individual is to be prescribed a particular drug.Use of propensity scores offers a method of reducing selection bias and confounding in pharmacoepidemiological studies [19,20]. Propensity scores were estimated for all patients using conditional logistic regression, with statin prescription at the index date as the outcome, taking the matching into account.…”
Section: Discussionmentioning
confidence: 99%
“…Propensity scores are increasingly being used in pharmacoepidemiologic studies to control for confounding (15). The propensity score is calculated as the probability of receiving one treatment compared with another, i.e., a TNF␣ antagonist versus a nonbiologic DMARD.…”
Section: Control For Potential Confoundingmentioning
confidence: 99%
“…If more covariates can be included in the propensity score model as compared with the conventional outcomes regression model (which is limited by the number of outcomes [16]), then adjustments in the propensity score may provide better adjustment for otherwise incompletely measured confounders. However, in practice, propensity score analyses have almost never produced results significantly different from those produced by conventional outcomes models in pharmacoepidemiology (15).…”
Section: Control For Potential Confoundingmentioning
confidence: 99%